Tree planting spade, gift from Class of 1906 (1906)
Tree planting spade, gift from class of 1906. Stored in a box with the Robert E. Kennedy Library groundbreaking spade. Used to plant graduating class trees each summer. Consult the archives for more information about the spade and class trees. See a detail of the spade's plaque here: http://digital.lib.calpoly.edu/rekl-84714